TUNNEL FIRE SPREAD PREVENTING APPARATUS - MURAOKA HIROSHI (2006)
PROBLEM TO BE SOLVED: To allow the passing of vehicles even when a tunnel inside is partitioned by a fire wall due to outbreak of fire. SOLUTION: The subject tunnel fire spread preventing apparatus is provided with an opening/closing unit 4 having a predetermined length and a canopy-shaped cross section according to the inner wall of a ceiling part of the tunnel 1, and a plurality of partition curtains 3 constituting a fire prevention wall body 8 having one end fixed to the ceiling part of the tunnel 1, partitioning the longitudinal direction of the tunnel with its suspension therefrom, and composed of flexible fire-resisting clothes. The respective partition curtains 3 are installed in the upper face of the canopy of the opening/closing unit in a fixed position of the opening/closing unit 4 to open a passage in the tunnel 1, and the respective partition curtains 3 are suspended from the ceiling face by the movement of the opening/closing unit 4 from the fixed position to partition the tunnel inside passage. COPYRIGHT: (C)2006,JPO&NCIPI